2003
DOI: 10.1097/00004872-200311000-00029
|View full text |Cite
|
Sign up to set email alerts
|

Coronary flow reserve in hypertensive patients with appropriate or inappropriate left ventricular mass

Abstract: In hypertensive patients free of coronary artery disease, the degree of reduction in CFR is associated with the excess of LVM beyond the values compensatory for individual haemodynamic load. This relation is also independent of the presence of LV hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 29 publications
3
32
0
2
Order By: Relevance
“…7,22 One speculation is that the excessive growth of LVM is associated with changes in myocardial structure, with a disproportionate increase in extracellular matrix and myocardial fibrosis. 25 Myocardial fibrosis could determine abnormalities in coronary microcirculation blood supply, contributing to myocardial ischemia, 26 diastolic filling, relaxation impairment, and favoring heart failure and/or supraventricular arrhythmias. In our study we could observe that, in patients with regression of inappropriate LVM, a significant increase in stroke volume was observed, whereas the opposite occurred in patients with inappropriate LVM development, possibly influencing the incidence of heart failure; 13 heart failure events occurred in patients with persistence or development of inappropriate LVM, and only 1 occurred in patients with persistently appropriate LVM.…”
Section: Discussionmentioning
confidence: 99%
“…7,22 One speculation is that the excessive growth of LVM is associated with changes in myocardial structure, with a disproportionate increase in extracellular matrix and myocardial fibrosis. 25 Myocardial fibrosis could determine abnormalities in coronary microcirculation blood supply, contributing to myocardial ischemia, 26 diastolic filling, relaxation impairment, and favoring heart failure and/or supraventricular arrhythmias. In our study we could observe that, in patients with regression of inappropriate LVM, a significant increase in stroke volume was observed, whereas the opposite occurred in patients with inappropriate LVM development, possibly influencing the incidence of heart failure; 13 heart failure events occurred in patients with persistence or development of inappropriate LVM, and only 1 occurred in patients with persistently appropriate LVM.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, increased coronary resistance and impaired CFR has been reported in hypertensive subjects with LVH vs those without, using trans-oesophageal echocardiography and adenosine infusion. 42 Reduced coronary flow velocity reserve has been reported in hypertensives with vs those without echocardiographic LVH using trans-thoracic echocardiography, 43 a technique that allows evaluation of intracoronary peak velocities but not coronary dimension change and therefore cannot be use to extrapolate changes in myocardial blood flow. Although evidences have been accumulated on the fact that CFR is impaired in many types of pathologic hypertrophy, the anatomic or biochemical basis for these observations remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in this report we used the peak coronary velocity in early diastole assuming that the temporal peak velocity is proportional to the temporal mean velocity taken over the cardiac cycle. This assumption has been validated in man (Saraste et al, 2001), and the use of peak diastolic velocity in place of average diastolic velocity in the estimation of coronary reserve is becoming more common and accepted in clinical studies because maximum velocity is more robust, easier to measure, and less affected by noise, cardiac motion, and flow in neighboring vessels Galderisi et al, 2003;Rigo, 2005;Santagata et al, 2005;Saraste et al, 2001). In the studies reported here we did not see significant changes between baseline and hyperemia in the waveform of coronary velocity or in the ratio of systolic to diastolic velocity.…”
Section: Factors Affecting Baseline and Hyperemic Velocitiesmentioning
confidence: 97%